A Case Study on Education – Employment Profile of Women In an Industrial State: The Changing Role of Women in the Industrial State (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Women constitute around forty-nine per cent of theavailable human resource in India. Out of which a significant percentage, i.e.22.7 per cent are represented in the work force and play crucial roles in theproduction processes in all sectors of the transitional economy. However, theform and extent of their productive work participation have changed over theyears, mostly because of the changes in the methodology of production caused bythe various phases of industrialization, urbanization, the emergingtechno-economic environment of the country and specific professionalrequirements of the labour force, viz. education, training, etc.